The unicorn and the lake - Mayer, Marianna (New York : Dial Books for Young Readers, 1987)
When a serpent poisons the lake where all the animals drink, only the unicorn has the power to save them.
Reprint. Originally published: 1982.
Keywords: Unicorns -- Fiction; Snakes -- Fiction